Inibidores de dipeptidilpeptidase IV no tratamento da doença Hepática gordurosa não alcoólica - Santos, Lucas Ribeiro dos [UNIFESP] (2019)
Introduction: Hepatic steatosis is a frequent disease, which may be secondary to several pathologies; and non-alcohol-related alcohol and other causes, such as autoimmune diseases and infiltrative diseases, afflicting, especially, obese and insulin resistant patients. The diagnosis can be made through imaging tests such as ultrasound, computed tomography and magnetic resonance imaging. Despite the high prevalence and relation with complications such as cirrhosis and hepatocarcinoma, there is no specific treatment, being recommended lifestyle changes with weight loss; the use of medications such as pioglitazone and vitamin E may decrease activity, and the other distinct medications have already been tested for the same purpose. Objective: To determine the inhibition of inhibition of dipeptidylpeptidase IV in the treatment of NAFLD and NAFLD. METHODS: We searched the electronic databases of the Cochrane Library, MEDLINE, EMBASE and LILACS without data limits, as well as the reference lists of the included studies and the main editors on the subject were verified, regardless of the publication status and the Publication language, and were selected 9 studies to the end of the evaluation of methodological quality. Results: in 7 studies that were used to compile data via meta-analysis, for 3 outcomes. i DPP-IV showed an ALT-reducing power of MD -10.83 [95% CI 35.23 to 13.57] at 3 months and MD -9.27 [95% CI 10.92 to -7.62] at 6 months of intervention, as well as reduction of hepatic steatosis via MRI of SMD 0.10 [95% CI 0.31 to 0.50]; the overall incidence of adverse events was very low. The studies were generally of low and very low quality by the GRADE evaluation. Conclusion: Because of the poor overall quality of the studies, i DPP-IV did not show efficacy on inflammatory markers or fibrosis in patients with NAFLD. More rigorous randomized clinical trials with adequate inclusion criteria are still necessary to evaluate the efficacy of i DPP-IV in NAFLD.